2022
DOI: 10.1136/bjsports-2022-106021
|View full text |Cite
|
Sign up to set email alerts
|

Healthspan and chronic disease burden among young adult and middle-aged male former American-style professional football players

Abstract: ObjectiveTo examine the relationships between age, healthspan and chronic illness among former professional American-style football (ASF) players.MethodsWe compared age-specific race-standardised and body mass index-standardised prevalence ratios of arthritis, dementia/Alzheimer’s disease, hypertension and diabetes among early adult and middle-aged (range 25–59 years) male former professional ASF players (n=2864) with a comparator cohort from the National Health and Nutrition Examination Survey and National He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Former athletes had lower glucose levels than controls. 42 43 51 52 Former athletes also had a lower prevalence of diabetes, 50 hyperglycemia 43 and metabolic syndrome 42 than controls. One study found that former NFL football players had lower high-sensitivity C reactive protein compared with controls.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Former athletes had lower glucose levels than controls. 42 43 51 52 Former athletes also had a lower prevalence of diabetes, 50 hyperglycemia 43 and metabolic syndrome 42 than controls. One study found that former NFL football players had lower high-sensitivity C reactive protein compared with controls.…”
Section: Resultsmentioning
confidence: 95%
“…Most studies were cross-sectional, evaluated males only, and were conducted in Europe (table 1, online supplemental appendix 2). Nine studies included former athletes from multiple sports with a mix of endurance and team sports,33 42–49 while three studies included only American football50–52 and three studies included only soccer (ie, football) 53–55. Most (12 of 20) studies involved athletes who had competed at national and international competitions, including seven studies on Olympic athletes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations